MaTAR25: a long non-coding RNA involved in breast cancer progression. (4th March 2021) - Chang, Kung-Chi; Spector, David L.
ABSTRACT: We recently reported on the role of Mammary Tumor Associated RNA 25 ( MaTAR25 ) in mammary tumor cell proliferation, migration, and invasion. MaTAR25 interacts with transcriptional activator protein Pur-beta (Purb) to regulate its downstream targets such as Tensin1 in trans . The human ortholog of MaTAR25, LINC01271, is upregulated with human breast cancer stage and metastasis.